PENGARUH DISIPLIN KERJA DAN KOMITMEN ORGANISASI TERHADAP KINERJA GURU MADRASAH IBTIDAIYAH - Mustolihudin; Sita Husnul Khotimah (Jurnal Pendidikan Dasar, 2020)
This study aims to determine and analyze the effect of work discipline and organizational commitment on the performance of teachers at MI Mumtaza Islamic School Pondok Cabe, South Tangerang, either individually or collectively. This study used a survey method with a quantitative approach. The study population was all teachers of MI Mumtaza Islamic School Tangerang Selatan, totaling 115, with a sample of 45 teachers. Data were collected using a questionnaire on work discipline, organizational commitment and teacher performance. Data were analyzed using descriptive and inferential statistics, while hypothesis testing used multiple linear regression tests. The results of the study: 1) There is an influence between work discipline on teacher performance with a correlation coefficient value of 0.783, this shows that work discipline affects teacher performance by 61% with a strong category, 2) There is an influence between organizational commitment on teacher performance and the coefficient value. The correlation is 0.487, this shows that organizational commitment affects teacher performance by 24% with a low category, 3) There is an influence between work discipline and organizational commitment simultaneously on teacher performance as indicated by the correlation coefficient value of 0.728. This shows that together work discipline and organizational commitment have an effect of 53% on teacher performance in the medium category.